Literatur Review: Analisis Pemahaman Pasien terhadap Sistem Rujukan Berjenjang Jaminan Kesehatan Nasional (JKN) - Mariani, Tia; Rahma, Shinta; Amira, Anisa Puti; Gurning, Fitriani Pramita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Health is one of the basic needs of humans to live decently and productively. Therefore, controlled health services are needed in terms of cost and quality, because every human being, whether rich or poor, living in a developed or developing country, is always faced with life-threatening risks. The implementation of the referral system in Indonesia is regulated in a tiered or tiered form, namely First, Second, and Third level Health Facilities, which are interconnected. Until now, the implementation of the tiered referral system is still being perfected, especially related to the understanding of BPJS participants about the tiered referral system. Many participants who come to PPK I or PPK II do not understand the tiered referral mechanism. The method used in this research is the Literature Review method, which is a systematic, reproducible, and explicit method for identifying, evaluating, and synthesizing the works and thoughts of researchers. The results of this study indicate that many people or patients still do not understand the tiered referral system in the national health insurance (JKN). After reviewing five articles, it is concluded that many people or patients still do not understand the tiered referral system in the national health insurance (JKN). This is due to the lack of understanding of health workers about the vertical and horizontal referral system, as well as the lack of socialization about the referral system to patients, explanations from health workers are only obtained when requesting a referral and through posters at community health centers.